Urinoma complicating uretric calculi - Gill, Simran Kaur; Arora, Bhavinder Kumar (International Surgery Journal, 2024)
Urinoma is a rare but significant complication of renal calculi and uretric calculi, characterized by the accumulation of urine outside the renal collecting system due to obstruction. This case report details a 62-year-old male who developed a urinoma secondary to obstruction caused by a large uretric stone. The report highlights the clinical presentation, diagnostic approach, management strategies, and the outcome.